First time FRS adoption among top Malaysian public listed companies / Najihah Marha Yaacob and Ayoib Che Ahmad - Yaacob, Najihah Marha; Che Ahmad, Ayoib (2012)
Globalization has led to greater demand for more uniform accounting standards throughout the world. A single global standard is vital for the investors who look for the best capital markets in which to invest, based on the financial reports available across the boundaries. International Accounting Standard Board (IASB) has taken an aggressive initiative to bring further convergence between local Generally Accepted Accounting Principles (GAAP) and international standards with the amendments of some existing standards and adopted certain new standards in the name of the International Financial Reporting Standards (IFRS). Nevertheless, the complexity on the issue of convergence with a single standard has been raised by many parties (Hoogendoorn, 2006; Bernhut, 2008). Similarly, the Malaysian's accounting bodies have also raised their anxiety as to whether the public listed companies are ready to encounter the major accounting transition. Therefore, this study tries to investigate the extent of FRS adoption among the Malaysian's top 100 listed companies. Using sample of 57 companies to represent the first annual reports to adopt 18 new or revised FRSs, this study reveals that all largest companies have promptly adhered to the FRS transition. Nevertheless, the level of adoption differs between the sample companies.